Artificial-intelligence powered app as learning aid in improving learning autonomy: Students’ perspective - Mahendra, Made Wahyu; Nurkamilah, Nurkamilah; Sari, Christine Permata (JEES (Journal of English Educators Society), 2023)
The disruption and development of technology has rapidly transformed the educational system these days. Its practicality has driven students to equip themselves with technological devices and software, particularly those with Artificial-intelligence. This study aimed at identifying students’ perspective on the implementation of Artificial-Intelligence Powered App as Learning Aid in Improving Learning Autonomy. Specifically, this study identified whether or not the use of Artificial-Intelligence Powered App as Learning Aid could change learners’ perspective on autonomous learning and improve their learning autonomy. Further, the perspective being investigated is related to learners perspective on their role in fostering autonomy as well as learners’ perspective toward the teachers’ role. The researchers conducted the study by following a collaborative action research. The data of the study were collected using questionnaires and semi structured interview. Then, the results of the questionnaires were analyzed quantitatively and the results of the interview were analyzed qualitatively. This study finds out that incorporating artificial intelligence powered apps has successfully changed learners’ perspective on autonomous learning. Besides, the use of artificial intelligence powered app also works positively in fostering learners’ autonomy. Since this study was conducted using action research method, the result of the study cannot be generalized to a larger population. Thus, an experimental study that apply inferential statistics analysis is needed to support the results of the study. HIGHLIGHTS: One of the challenges in fostering learner autonomy is making them understand of the need to be autonomous. Learners initially thought that teachers should spoon-feed them the learning materials. AI powered apps like Mondly has the potential to help students understand their roles and teacher’s roles during learning by providing them features that encourage autonomous learning activities, such as planning, monitoring and evaluating their learning.